P11.10 Anal and oropharyngeal sti surveillance among men who have sex with men in guatemala. (13th September 2015) - Mendizabal-Burastero, R; Vargas, C; Galindo-Arandi, C; Loya-Montiel, I; Valenzuela, C; Morales-Miranda, S
Abstract : Introduction: Sentinel Surveillance and STI Control (VICITS) strategy is implemented in public health clinics for key populations, including men who have sex with men (MSM) in Guatemala. Although oral and anal sexually transmitted infections (STI) are important public health issues, they are not included in national treatment guidelines. Evidence of disease burden is needed for decision making. We analysed STI prevalence in oral, anal and urethral samples among MSM who attended VICITS clinics in Guatemala in 2014. Methods: Clients were male, ≥18 years old, who reported sexual relations with another man in the last 12 months, and who was seen at one of four VICITS clinics between June–December 2014. Sociodemographic data, risk behaviour, and biological data were abstracted from routine clinical intake forms stored in the in VICITS information system. Laboratory results from urethral, anal and oropharyngeal samples were collected. Digene Hybrid Capture II (Qiagen) was used for detection of C. trachomatis (CT) and N. gonorrhoeae (NG). Data analysis was performed using Stata 11.0. Results: A total of 524 MSM were included in the analysis. The median age was 25 years old (IQR 21–30), 67.4% reported receptive anal sex in the last 30 days, and 56.6% reported condom use at last receptive anal sex. About 30% reported at least one STI and 4.6% reported at least 2 STIs in the last 3 months. The prevalence of anal CT was 4.7%, anal NG was 4.4%, oral CT was 2.2%, oral NG was 25.4%, urethral CT was 1.9%, and urethral NG was 4.1%. Overall, 77.7% of infections were caused by NG. Conclusion: We found a high prevalence of NG, especially in oral and anal samples among MSM attending VICITIS clinics. Our findings underscore the need to include anal and oral STIs in national treatment guidelines. Innovative strategies to increase adoption of condom use in anal and oral sex among MSM and the evaluation of resistance profile for NG are urgently needed in Guatemala. Disclosure of interest statement: We declare that we have no conflicts of interest.